Constitutive release of purines in control of vascular contractility - Alqarni, Aali (2023)
Most large and medium sized arteries are surrounded by perivascular adipose tissue (PVAT). PVAT was once considered a passive structural component of the vascular wall, not an active regulator of vascular homeostasis. However, PVAT releases several active mediators that have a paracrine effect on vascular tone. Adipocytes express P2X and P2Y receptors, whose activation influences a number of adipocyte functions including the release of adipokines. Adipocytes can also release nucleotides to control adipocyte activity. It is unknown whether this occurs in PVAT and alters the tone of the adjacent vasculature. The constitutive release of purines in blood vessels is relatively unknown. However, it is important to understand vascular control mechanisms to offer new therapeutic approaches for cardiovascular diseases such as hypertension. The main purpose of this study was to determine if nucleotides (ATP/UTP) are released constitutively from PVAT to regulate the vascular tone of porcine mesenteric artery. Further investigation was performed to examine the possibility that P2X, P2Y, and adenosine receptors may contribute to the vasorelaxant effect induced by AR-C118925XX (a P2Y2 receptor antagonist). Additionally, I investigated whether the nucleotides ATP and UTP activate P2Y receptors to release adiponectin and leptin from 3T3-L1 adipocytes. I also examined whether the anti-contractile effect of PVAT in response to ATP and UTP in porcine splenic arteries may be associated with adiponectin release.